Perkembangan Iman Rasul Cilik pada Masa Pandemi Covid-19 Paroki Santa Perawan Maria dari Gunung Karmel Ijen Malang - Sogen, Dimas Sandy Himawan; Firmanto, Antonius Denny; Aluwesia, Ninik Wijayati (Sekolah Tinggi Pastoral IPI Malang, 2021)
English: The Covid-19 pandemic raises problems that have a wide impact on society. The impact is also felt by the little apostle coaches in fostering the faith of children who are members of the little apostolic community. The development of the faith of the little apostles is very important for the Church. The Church makes every effort through companions to build up the little apostles. There are many challenges due to the pandemic and the rapid development of technology. This situation forms a pattern of thinking and relationship patterns that tend to be individualistic. This change requires the counselors to find the right teaching method to build up the faith of the little apostles. Exemplary and proper teaching is needed for the development of the faith of the little apostle. Formers and proper teaching can be given by formers and parents for the future development of the Church. Bahasa Indonesia: Pandemi Covid-19 menimbulkan persoalan yang berdampak luas bagi masyarakat. Dampaknya juga dirasakan oleh para pembina rasul cilik dalam membina iman anak-anak yang tergabung dalam komunitas rasul cilik. Perkembangan iman para rasul cilik menjadi hal yang sangat penting bagi Gereja. Gereja mengusahakan segala cara melalui para pendamping untuk membina rasul cilik. Banyak tantangan akibat pandemi dan perkembangan teknologi yang begitu pesat. Situasi ini membentuk pola pikir dan pola relasi yang cenderung individulistis. Perubahan ini menuntut para pembina menemukan metode pengajaran yang tepat untuk membina iman rasul cilik. Keteladan dan pengajaran yang tepat sangat dibutuhkan untuk perkembangan iman rasul cilik. Keteladan dan pengajaran yang tepat bisa diberikan oleh para pembina dan orang tua demi perkembangan Gereja di masa depan.